1990
DOI: 10.1088/0031-8949/42/5/006
|View full text |Cite
|
Sign up to set email alerts
|

Lifetimes of transitions in the visible range in neutral sulphur

Abstract: Radiative lifetimes of 8 different multiplets in the visible range in neutral sulphur have been directly measured using the High Frequency Deflection technique. These lifetimes have not been experimentally studied earlier. The results are compared to Coulomb approximation calculations and semiempirical estimates of the associated oscillator strengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
3
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
6
3
0
Order By: Relevance
“…Large discrepancies also occur for the lifetime of the 3s 2 3p 3 ( 4 S o )4s 5 S o 2 level. Our results tend to agree with the same order of magnitude as that of Mason [29] whereas the measurement of Delalić et al [10] reported nearly half of our value. Nevertheless, this [10] measured value (9200 ns) was analysed [29] to be the maximum value their experimental setup can reach.…”
Section: Levelsupporting
confidence: 92%
See 2 more Smart Citations
“…Large discrepancies also occur for the lifetime of the 3s 2 3p 3 ( 4 S o )4s 5 S o 2 level. Our results tend to agree with the same order of magnitude as that of Mason [29] whereas the measurement of Delalić et al [10] reported nearly half of our value. Nevertheless, this [10] measured value (9200 ns) was analysed [29] to be the maximum value their experimental setup can reach.…”
Section: Levelsupporting
confidence: 92%
“…Comparison of radiative lifetimes (in nanoseconds) for some sulfur levels. The superscripts in the last column (a), (b), (c), (d) and (e) stand for the references [10], [16], [17], [28] and [29] respectively. ZB: Zatsarinny and Bartschat [18].…”
Section: Llmentioning
confidence: 99%
See 1 more Smart Citation
“…Federman and Cardelli [6] reported a number of f-values for a wide range of wavelengths. Earlier measurements of f-values for transitions among some of the above multiplets were also reported by Savage and Lawrence [7], Mü ller [8], Delalić et al [9], and Doering [10].…”
Section: Introductionsupporting
confidence: 58%
“…However, lifetime measurements of higher electron configurations for the lighter elements in the oxygen subgroup have been performed. Kr611 et al in 1985 used two-photon excitation on oxygen atoms [12] and Delalic et al in 1990 used electron-beam excitation on sulphur [13]. In the present work we have continued our investigations of radiative lifetimes of the tellurium atom by using step-wise pulsed dye laser exci- tations.…”
Section: Introductionmentioning
confidence: 81%